2019
DOI: 10.14710/jitaa.44.2.204-212
|View full text |Cite
|
Sign up to set email alerts
|

Beef cattle farmers behavior toward biosecurity

Abstract: Beef cattle are meat producers which are beneficial to humans. The purpose of this study was to identify and to control the behavior of beef cattle farmers towards biosecurity in Lamasi District - Luwu Region, South Sulawesi Province. This type of research was descriptive research. The research method was survey to participatory research and the Focus Group Discussion. Total sample was 50 respondents. Data were obtained through interview using questionnaires and observations. Data were analyzed using descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The organisation-level examined the chicken industry, in which social relationships, resource supply and production condition issues occurred that are associated with adopting biosecurity measures. While Ellis-Iversen et al ( 59 ) and Enticott and Wilkinson ( 60 ) indicated that farmers' biosecurity decisions are influenced by economic pressure and organisation culture from society and industry, Barclay ( 57 ) and Lestari et al ( 61 ) suggested that weather and agricultural space/environment can affect the implementation of biosecurity. Four themes identified in the interviews, as shown in Table 1 , including “Production conditions”, “Domestic market access”, “The supply of vaccines and medication” and “Industry development”, are associated with the adoption of biosecurity measures at the organisation-level.…”
Section: Resultsmentioning
confidence: 99%
“…The organisation-level examined the chicken industry, in which social relationships, resource supply and production condition issues occurred that are associated with adopting biosecurity measures. While Ellis-Iversen et al ( 59 ) and Enticott and Wilkinson ( 60 ) indicated that farmers' biosecurity decisions are influenced by economic pressure and organisation culture from society and industry, Barclay ( 57 ) and Lestari et al ( 61 ) suggested that weather and agricultural space/environment can affect the implementation of biosecurity. Four themes identified in the interviews, as shown in Table 1 , including “Production conditions”, “Domestic market access”, “The supply of vaccines and medication” and “Industry development”, are associated with the adoption of biosecurity measures at the organisation-level.…”
Section: Resultsmentioning
confidence: 99%
“…They are the most wealthy farmers with the highest education levels. As observed by Lestari et al (2019) and Abdullah et al (2021), large-scale cattle farmers don't seem to perceive biosecurity or innovation incentives as a real advantage. They can sell their cattle at any time, giving them a secure business -as confirmed through communication with Universidad Nacional de Costa Rica and local cattle farmers.…”
Section: Farmer Preferences Regarding Vanilla Cultivationmentioning
confidence: 95%
“…Biosecurity is essential in beef cattle farming to prevent unwanted diseases and ensure healthy and clean cattle. Vaccinations, animal traffic management, and sanitation are the things that must be given more attention in implementing biosecurity on the farm (Lestari et al, 2019). Biosecurity on the farm aims to avoid transmitting diseases, including Anthrax and other high-risk diseases to humans (Lestari et al, 2019).…”
Section: Biosecurity and Vaccinationmentioning
confidence: 99%
“…Vaccinations, animal traffic management, and sanitation are the things that must be given more attention in implementing biosecurity on the farm (Lestari et al, 2019). Biosecurity on the farm aims to avoid transmitting diseases, including Anthrax and other high-risk diseases to humans (Lestari et al, 2019). Farmers are usually informed about biosecurity but are not ready to implement it on their farms.…”
Section: Biosecurity and Vaccinationmentioning
confidence: 99%